Liquid-type lead-acid battery

The liquid lead-acid battery design, featuring a negative electrode material with high sulfur content organic antishrinkage agents and graphite, addresses the issue of electrolyte reduction and enhances high temperature resistance and PSOC performance by optimizing electrode plate spacing and separator thickness.

JP2025039252APending Publication Date: 2025-03-21GS YUASA CORP
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023146205
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-09-08
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

In liquid lead-acid batteries, the use of organic shrinkage inhibitors with high sulfur element content leads to increased reduction in electrolyte amount, compromising battery performance and lifespan, especially under high temperature conditions and partial state of charge (PSOC) operations.

Method used

A liquid lead-acid battery design that incorporates a negative electrode material with an organic antishrinkage agent having a sulfur element content of 2000 μmol/g or more, combined with graphite, where the graphite content is between 0.5% by mass and 2.0% by mass, and the difference between the total distance between positive and negative electrode plates and the total thickness of the separator is less than 0.10 mm.

Benefits of technology

This configuration reduces the amount of electrolyte reduction, enhances high temperature resistance, and improves the battery's partial state of charge (PSOC) lifetime performance by promoting balanced reactions and reducing gas generation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025039252000001_ABST
    Figure 2025039252000001_ABST
Patent Text Reader

Abstract

SOLUTION: To provide a liquid-type lead-acid battery including an electrode plate group, an electrolyte, and a cell chamber accommodating the electrode plate group and the electrolyte, the electrode plate group including positive electrode plates, negative electrode plates, and separators interposed between the positive electrode plates and the negative electrode plates, a difference (s-t) between a total s of a distances between the positive and negative electrode plates facing each other in the electrode plate group and a total t of the thicknesses of the separators being less than 0.10 mm, the negative electrode plate including a negative electrode material, the negative electrode material including an organic antishrinkage agent having a sulfur element content of 2000 μmol / g or more, and graphite, a content of the graphite in the negative electrode material ranging from 0.5 mass% or more to 2.0 mass% or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to flooded lead-acid batteries. [Background technology]

[0002] Lead-acid batteries are used in a variety of applications, including automotive and industrial use. Lead-acid batteries include negative and positive plates, a separator (or mat), and an electrolyte. Each plate includes a current collector and an electrode material. In order to improve the performance of lead-acid batteries, various attempts have been made, such as improving the separator and using additives in the plates.

[0003] Patent Document 1 proposes a lead-acid battery comprising: an electrode plate group including a negative electrode plate, a positive electrode plate, and a separator interposed between the negative electrode plate and the positive electrode plate; and an electrolyte; the negative electrode plate includes a negative electrode material including a first carbon material and a second carbon material; the first carbon material has a particle diameter of 32 μm or more; the second carbon material has a particle diameter of less than 32 μm; a ratio of powder resistance R2 of the second carbon material to powder resistance R1 of the first carbon material: R2 / R1 is 20 or more and 200 or less; and a distance D between the positive electrode plate and the negative electrode plate and a maximum thickness T of the separator satisfy -0.1 mm≦DT≦0.1 mm.

[0004] Patent Document 2 discloses a battery container having a cell chamber and an open top, an electrode group and an electrolyte contained in the cell chamber, and a lid for closing the opening. The electrode group has a negative electrode and a positive electrode, and the negative electrode contains a Pb component, lignosulfonic acid and / or a salt thereof, and a cellulose ester having a specific surface area of ​​10.0 m. 2 / g or less, and a carbon material having a negative electrode active material containing the same.

[0005] Patent Document 3 discloses a battery comprising a negative electrode plate, a positive electrode plate, and an electrolyte, the negative electrode plate comprising a negative electrode current collector and a negative electrode material, and in the Log differential pore volume distribution of the negative electrode material, a: a region with a pore diameter of 1 to 3 μm is defined as region P, b: a region with a pore diameter of 6 to 15 μm is defined as region Q, c: the maximum value of the Log differential pore volume in region P is defined as region P, and d: the maximum value of the Log differential pore volume in region Q is defined as region Q. We propose a lead-acid battery in which, in a light-load life test in which charging and discharging are repeated for 10 minutes at a constant voltage of 0.47 V / cell and a maximum current of 25 A at a test temperature of 75°C, the Log differential pore volume distribution of the negative electrode material after 1,220 cycles has a peak p in the P region corresponding to the maximum value P and a peak q in the Q region corresponding to the maximum value Q, and the maximum value P and the maximum value Q satisfy 0.25≦P / (P+Q)≦0.63.

[0006] Patent Document 4 discloses a flooded lead-acid battery having a configuration in which a negative electrode plate having a negative electrode active material packed in a negative electrode current collector and a positive electrode plate having a positive electrode active material packed in a positive electrode current collector are stacked with a separator interposed therebetween, and the plate group is housed in a battery case together with an electrolyte, and charging is performed intermittently and high-rate discharging to a load is performed in a partially charged state. At least a carbonaceous conductive material and an organic compound that suppresses coarsening of the negative electrode active material due to charging and discharging are added to the negative electrode active material, and the positive electrode plate has a unit plate pack volume [cm 3 ] Total surface area of ​​positive electrode active material [m 2 ] to 3.5 to 15.6 [m 2 / cm 3 The present invention proposes a lead-acid battery characterized in that the lead-acid battery is configured to have a current limit within the range of [ ]. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] International Publication No. 2019 / 188056 [Patent Document 2] International Publication No. 2019 / 077657 [Patent Document 3] International Publication No. 2019 / 225161 [Patent Document 4] International Publication No. 2011 / 142072 Summary of the Invention [Problem to be solved by the invention]

[0008] The negative electrode plate of a lead-acid battery may contain an organic shrinkage inhibitor. Examples of the organic shrinkage inhibitor include lignin compounds and synthetic organic shrinkage inhibitors. Synthetic organic shrinkage inhibitors have a relatively high sulfur content (e.g., 2000 μmol / L or more). Compared to the use of lignin compounds, the use of synthetic organic shrinkage inhibitors makes it easier to obtain excellent high temperature resistance. However, in flooded lead-acid batteries, the use of an organic shrinkage inhibitor with a high sulfur content (e.g., 2000 μmol / L or more) creates a tradeoff in that the amount of electrolyte lost increases. [Means for solving the problem]

[0009] One aspect of the present disclosure is a flooded lead-acid battery, The flooded lead-acid battery includes a plate group, an electrolyte, and a cell chamber that accommodates the plate group and the electrolyte, the electrode plate group includes a positive electrode plate, a negative electrode plate, and a separator interposed between the positive electrode plate and the negative electrode plate, The difference (st) between the total distance s between the positive electrode plate and the negative electrode plate facing each other in the electrode plate group and the total thickness t of the separator is less than 0.10 mm; The negative electrode plate includes a negative electrode material, The negative electrode material includes an organic shrinkage preventer having a sulfur element content of 2000 μmol / g or more and graphite, The negative electrode material has a graphite content of 0.5% by mass or more and 2.0% by mass or less. Effect of the Invention

[0010] In a lead-acid battery, the amount of electrolyte loss can be reduced. [Brief description of the drawings]

[0011] [Figure 1] 1 is a partially cutaway exploded perspective view illustrating an outline of the external appearance and internal structure of a lead-acid battery according to one aspect of the present invention. FIG. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The negative electrode material of a lead-acid battery is easily deteriorated in a high-temperature environment, and an organic shrink-proofing agent having a high sulfur content (for example, a sulfur content of 2000 μmol / L or more) exhibits excellent high-temperature resistance compared to an organic shrink-proofing agent having a low sulfur content (for example, a sulfur content of less than 2000 μmol / L) such as a lignin compound. Hereinafter, an organic shrink-proofing agent having a sulfur content of 2000 μmol / L or more may be referred to as a first organic shrink-proofing agent, and an organic shrink-proofing agent having a sulfur content of less than 2000 μmol / L may be referred to as a second organic shrink-proofing agent. The reason why excellent high-temperature resistance is obtained when the first organic shrink-proofing agent is used is that the first organic shrink-proofing agent has a high effect of suppressing deterioration of the negative electrode material in a high-temperature environment, and the large specific surface area of ​​the negative electrode material is maintained, thereby obtaining excellent discharge performance. On the other hand, when the first organic shrink-proofing agent is used, the reactivity with protons during overcharging is high compared to when the second organic shrink-proofing agent is used, and the amount of hydrogen gas generated is large, so that the decrease in electrolyte is significant. Hereinafter, the reduction in the electrolyte may be referred to as "liquid reduction", and the amount of reduction in the electrolyte may be referred to as "amount of reduced electrolyte".

[0013] In addition, flooded lead-acid batteries are sometimes used in a state of insufficient charge called a partial state of charge (PSOC). When a lead-acid battery is used in PSOC, stratification tends to progress, in which the electrolyte density at the top of the battery is gradually lower and the electrolyte density at the bottom of the battery is gradually higher. As stratification progresses, accumulation of lead sulfate becomes prominent at the bottom of the negative electrode plate, and sulfation, in which lead sulfate crystals are formed, tends to occur. This leads to a decrease in capacity, and the electrode plate deteriorates due to uneven charge and discharge reactions, shortening the life of the lead-acid battery. For example, in idling stop applications, high life performance in PSOC is required. Hereinafter, the life performance in PSOC may be referred to as PSOC life performance. In this specification, idling stop may be simply referred to as IS. An example of an IS application is an idling stop system (Idle Reduction System) vehicle.

[0014] In view of the above, (1) a flooded lead-acid battery according to one aspect of the present invention includes a plate assembly, an electrolyte, and a cell chamber that accommodates the plate assembly and the electrolyte. The plate assembly includes a positive plate, a negative plate, and a separator interposed between the positive plate and the negative plate. The difference (st) between the total distance s between the positive plate and the negative plate facing each other in the plate assembly and the total thickness t of the separator is less than 0.10 mm. The negative plate includes a negative electrode material. The negative electrode material includes an organic shrinkage preventer (i.e., a first organic shrinkage preventer) having a sulfur element content of 2000 μmol / g or more, and graphite. The content of graphite in the negative electrode material is 0.5 mass% or more and 2.0 mass% or less. The flooded lead-acid battery is sometimes called a vented lead-acid battery.

[0015] When (st) ≧ 0.10 mm, the tendency of liquid loss does not change even if the graphite content in the negative electrode material changes. When only the second organic shrink-proofing agent is used as the organic shrink-proofing agent, the tendency of the amount of liquid loss relative to the graphite content is almost the same in both cases of (st) < 0.10 mm and (st) ≧ 0.10 mm. However, when the first organic shrink-proofing agent is used in the case of (st) < 0.10 mm, the tendency of liquid loss at the graphite content = 0 mass% is almost the same as when (st) ≧ 0.10 mm, but when the graphite content is 0.5 mass% or more and 2.0 mass% or less, the liquid loss can be significantly suppressed.

[0016] In the lead-acid battery according to one aspect of the present invention, the reduction in the amount of electrolyte loss is believed to be due to the following (a) and (b). (a) By satisfying (st)<0.10 mm and by using a combination of the first organic shrinkage preventer and graphite, a gas absorption reaction occurs even though the battery is a flooded lead-acid battery. (b) The gas absorption efficiency of the first organic shrink-preventing agent is higher than the gas absorption efficiency of the second organic shrink-preventing agent.

[0017] Regarding the above (a), when (st) is less than 0.10 mm, the space between the plates is more closed, and oxygen generated in the positive plate is less likely to be released to the outside of the space between the plates. This increases the oxygen concentration in the space between the plates, and oxygen is efficiently supplied to the negative electrode. By combining graphite with the first organic shrinkage inhibitor, the functional groups of the first organic shrinkage inhibitor, such as sulfonic acid groups containing an S element, are easily adsorbed to the edge parts of the graphite, and the active points are covered with the synthetic organic shrinkage inhibitor. This suppresses side reactions involving the electrolyte at the edge parts of the graphite, and suppresses gas generation to a certain extent. Due to this interaction between the first organic shrinkage inhibitor and the graphite, the reaction between oxygen and hydrogen occurs in a balanced manner in the space between the plates. It is believed that this causes a gas absorption reaction to occur even though the battery is a flooded lead-acid battery. Note that, normally, when graphite is used, side reactions involving the electrolyte tend to occur at the active points of the edge parts, and therefore the amount of electrolyte loss tends to increase. In the flooded lead-acid battery according to one aspect of the present invention, loss of electrolyte can be suppressed by combining graphite with the first organic shrinkage preventer and by making (st)<0.10 mm.

[0018] When (st)<0.10 mm, the space between the plates is narrower and more closed than when (st)≧0.10 mm. When a rib (first rib) described later is formed on the separator, the space between the first rib, surrounded by the separator (more specifically, the base portion described later) and the positive plate, is also narrower and more closed. When the space between the plates becomes relatively smaller as in these cases, the closedness of the space is said to be relatively increased. It is believed that the increased closedness of the space between the plates causes a gas absorption reaction in the lead-acid battery according to one aspect of the present invention, even though it is a liquid type.

[0019] Regarding the above (b), when the first organic shrink-proofing agent is used, the specific surface area of ​​the negative electrode material is larger than when the second organic shrink-proofing agent is used, and the organic shrink-proofing agent is less likely to aggregate on the surface of the negative electrode plate. As a result, when the first organic shrink-proofing agent is used, the movement of oxygen on the negative electrode plate is less likely to be hindered than when the second organic shrink-proofing agent is used, and it is considered that the gas absorption efficiency is higher.

[0020] In addition, in the flooded lead-acid battery according to one aspect of the present invention, since the negative electrode material contains the first organic shrinkage inhibitor, higher high temperature resistance can be obtained compared to the case where the negative electrode material contains the second organic shrinkage inhibitor. Therefore, even when the battery is overcharged at a high temperature (e.g., 50°C or higher and 80°C or lower) and then discharged at a high rate, deterioration of the negative electrode material is suppressed, so that a long discharge duration can be ensured. Therefore, both high high temperature resistance and excellent effect of suppressing loss of liquid can be achieved.

[0021] (2) In the above (1), the difference (st) may be 0.07 mm or less. In this case, the amount of liquid loss can be further reduced.

[0022] (3) In the above (1) or (2), in a cross section of the flooded lead-acid battery parallel to the bottom of the cell chamber, the ratio Ra (=Se / Sg=(S1-Sg) / Sg) of the area (Se) obtained by subtracting the cross-sectional area (Sg) of the plate group from the cross-sectional area (S1) inside the cell chamber to the cross-sectional area (Sg) of the plate group may be 0.20 or less. In this case, the amount of electrolyte loss can be further reduced. The area (=Se=S1-Sg) obtained by subtracting the cross-sectional area of ​​the plate group from the cross-sectional area inside the cell chamber corresponds to the cross-sectional area of ​​the electrolyte present outside the outer edge of the plate group (outside the plate group) in the above cross section (in other words, the electrolyte surrounding the plate group in the cell chamber in which the plate group is accommodated). Therefore, it can be said that when Ra≦0.20, the amount of electrolyte present outside the plate group is smaller than when Ra>0.20. When Ra≦0.20, the amount of oxygen generated in the positive plate that migrates to the electrolyte outside the electrode assembly is smaller than when Ra>0.20, so a high concentration of oxygen can be retained between the electrodes. Therefore, when Ra≦0.20, more oxygen is supplied to the negative plate than when Ra>0.20, so it is thought that the gas absorption reaction occurs more easily. In addition, when Ra≦0.20, the PSOC life performance is significantly improved compared to when Ra>0.20. This is thought to be because the relatively small amount of electrolyte outside the electrode assembly suppresses stratification and deterioration of the electrode plates.

[0023] (4) In any one of the above (1) to (3), the separator may have at least a rib (first rib) protruding toward the positive electrode plate. The presence of the first rib increases the sealing of the space surrounded by the separator and the positive electrode plate. Since the oxygen concentration in this space increases, a large amount of oxygen is easily supplied to the negative electrode plate. Therefore, the gas absorption reaction occurs more easily, and the amount of liquid loss can be further reduced. The separator may have a rib (second rib) protruding toward the negative electrode plate as necessary. The first rib is formed, for example, in a portion of the separator facing a portion where the positive electrode material is present. The second rib is formed, for example, in a portion of the separator facing a portion where the negative electrode material is present. The separator usually has a base portion. In a separator having a rib, the rib protrudes from the surface of the base portion. The base portion of the separator refers to a portion of the separator that does not include protrusions such as ribs, and refers to a sheet-like portion that defines the outer shape of the separator.

[0024] (5) In the above (4), the average spacing between the first ribs may be 1.0 cm or less. In this case, the space between the separator and the positive electrode plate between the adjacent first ribs becomes more closed, which facilitates the gas absorption reaction, thereby further reducing the amount of liquid loss.

[0025] (6) In any one of the above (1) to (5), the graphite may not contain iron (Fe) element, or the content of Fe element in the graphite may be 110 ppm or less by mass. In this case, the hydrogen generation potential is unlikely to be reached, and the generation of hydrogen gas is reduced. This makes it easier to balance oxygen and hydrogen, and the gas absorption reaction is more likely to proceed efficiently, thereby further reducing the amount of liquid loss.

[0026] The flooded lead-acid battery according to one aspect of the present invention will be described in more detail below, including the above (1) to (6). At least one selected from the components described below can be arbitrarily combined with at least one of the above (1) to (6) for the flooded lead-acid battery according to one aspect of the present invention, as long as such combination is technically possible.

[0027] [Liquid lead acid battery] In a flooded lead-acid battery according to one aspect of the present invention, the difference (st) is less than 0.10 mm. When the difference (st) is this small, the amount of liquid loss can be reduced by the negative electrode material including a first organic shrinkage preventer and the graphite content in the negative electrode material being within a specific range. From the viewpoint of further reducing the amount of liquid loss, the difference (st) may be 0.07 mm or less, or may be 0.05 mm or less. From the viewpoint of reducing permeation short-circuiting and suppressing stratification, the difference (st) may be, for example, -0.15 mm or more, or -0.10 mm or more.

[0028] The difference (st) may be -0.15 mm or more (or -0.10 mm or more) but less than 0.10, -0.15 mm or more (or -0.10 mm or more) but 0.07 mm or less, or -0.15 mm or more (or -0.10 mm or more) but 0.05 mm or less.

[0029] (Measurement of difference (st)) The difference (st) is measured using a plate group taken out of a fully charged lead-acid battery. The total distance s between the opposing positive and negative plates in the plate group is the length between the outer surfaces of the plates at both ends in the direction parallel to the stacking direction of the plate group minus the total thickness of the positive and negative plates, divided by (number of plates - 1) (unit: mm).

[0030] The thickness of each of the positive and negative plates is determined by the following procedure: Remove all positive and negative plates from the plate group. Measure the thickness of all positive plates in the plate group with a vernier caliper and average the thickness to determine the thickness of the positive plates. In a lead-acid battery with multiple plate groups, measure the thickness of the positive plates in one plate group located at the end and one plate group located near the center and average the thickness to determine the thickness (average value) of the positive plates. The thickness of the negative plates is determined in the same manner as for the positive plates.

[0031] The total thickness t of the separators in the electrode plate group is the total value (unit: mm) obtained by measuring the thickness of all the separators present between adjacent positive and negative electrode plates in the electrode plate group. The thickness of the separator is measured with a vernier caliper. If the separator has a rib (specifically, a first rib, or a first rib and a second rib) in the portion facing the electrode material, the thickness of the separator is measured in the portion where the rib is present. If the positions of the first rib and the second rib are misaligned, a vernier caliper is used to measure the sum s1 of the thickness of the base portion and the height of the first rib in the first rib portion, and the sum s2 of the thickness of the base portion and the height of the second rib in the second rib portion, and the thickness t of only the base portion is measured. b Measure s1+s2-t b The thickness of the separator is determined by measuring the thickness at multiple locations (for example, five locations) of the electrode plate assembly and averaging the measurements.

[0032] A separator sample for measurement (Sample A) is prepared by removing the sulfuric acid from a separator removed from a fully charged lead-acid battery by rinsing with water. The size of the separator is measured while the separator is wet with water within 10 minutes after rinsing.

[0033] If the battery includes a plurality of electrode plate groups, s and t are obtained for one of the outermost electrode plate groups and one of the electrode plate groups near the center, and st is calculated.

[0034] A flooded lead-acid battery includes at least one cell. The cell includes a plate assembly, an electrolyte, and a cell chamber that contains the plate assembly and the electrolyte. The plate assembly includes a positive electrode plate, a negative electrode plate, and a separator interposed between the positive electrode plate and the negative electrode plate.

[0035] In the flooded lead-acid battery, the plate group may include a plurality of positive electrodes, a plurality of negative electrodes, and a separator interposed between the positive electrodes and the negative electrodes. The positive electrodes and negative electrodes are alternately stacked with the separator interposed therebetween. The width direction of the plate group (hereinafter referred to as the "x direction") is a direction perpendicular to the stacking direction of the positive electrodes, negative electrodes, and separators (hereinafter referred to as the "y direction") and perpendicular to the up-down direction (vertical direction). The up-down direction (vertical direction) is defined as the z direction. Each direction is based on the arrangement direction of the lead-acid battery when in use.

[0036] A flooded lead-acid battery usually includes a battery case. The battery case has a bottom, a side wall rising from the periphery of the bottom, and a lid that closes the open end of the side wall. The inside of the battery case may be divided into a plurality of spaces (cell chambers) by partition walls. The inside of the battery case may be divided into a plurality of spaces (e.g., six) by partition walls that are parallel to each other. The interior of the battery case may be divided into a plurality of spaces (e.g., four or more) by a plurality of partition walls that cross each other. When the battery case is not divided into a plurality of cell chambers or does not have a cell chamber, the battery case is regarded as one cell chamber. Each cell chamber is formed, for example, such that the dimension X in the x direction (width direction of the electrode plate group) is larger than the dimension (group length) Y in the y direction (stacking direction) of the electrode plate group.

[0037] The components of the flooded lead-acid battery will be described in more detail below. (Positive plate) The positive electrode plate may be, for example, a paste-type positive electrode plate, which includes, for example, a positive electrode current collector and a positive electrode material.

[0038] The positive electrode current collector may be formed by casting lead (Pb) or a lead alloy, or may be formed by processing a lead sheet or a lead alloy sheet. Examples of the processing method include expanding and punching. It is preferable to use a lattice-shaped current collector as the positive electrode current collector because it is easy to support the positive electrode material.

[0039] As the lead alloy used for the positive electrode current collector, in terms of corrosion resistance and mechanical strength, Pb-Sb alloy, Pb-Ca alloy, Pb-Ca-Sn alloy are preferable. The positive electrode current collector may have a surface layer. The surface layer and the inner layer of the positive electrode current collector may have different compositions. The surface layer may be formed so as to cover the entire positive electrode current collector, or may be formed on a part of the positive electrode current collector. The surface layer may be formed only on the lattice part, the lug part, or the frame part of the positive electrode current collector.

[0040] The positive electrode material contained in the positive electrode plate usually contains a positive electrode active material (lead dioxide or lead sulfate) that develops capacity through an oxidation-reduction reaction. The positive electrode material may contain other additives as necessary.

[0041] Unformed paste-type positive plates are obtained by filling a positive current collector with a positive paste, aging it, and drying it. The positive paste is prepared by kneading lead powder, other additives (reinforcing materials (e.g., resin fibers), etc.), water, and sulfuric acid. These unformed positive plates are then formed to obtain positive plates.

[0042] The formation of the unformed positive plate may be carried out, for example, by placing a plate assembly including the unformed positive plate and an electrolyte containing sulfuric acid in a lead-acid battery container, and charging the plate assembly in a state in which the electrolyte permeates the plate assembly. However, the formation may also be carried out before assembling the lead-acid battery or the plate assembly.

[0043] (Negative plate) The negative plate includes a negative electrode material and typically includes a negative current collector.

[0044] The negative electrode current collector may be formed by casting lead (Pb) or a lead alloy, or may be formed by processing a lead sheet or a lead alloy sheet. Examples of the processing method include expanding and punching. It is preferable to use a lattice-shaped current collector as the negative electrode current collector because it is easy to support the negative electrode material.

[0045] The lead alloy used for the negative electrode current collector may be any of Pb-Sb alloy, Pb-Ca alloy, and Pb-Ca-Sn alloy. These lead or lead alloys may further contain at least one element selected from the group consisting of Ba, Ag, Al, Bi, As, Se, Cu, etc., as an additive element.

[0046] The negative electrode current collector may have a surface layer. The surface layer and the inner layer of the negative electrode current collector may have different compositions. The surface layer may be formed so as to cover the entire negative electrode current collector, or may be formed on a part of the negative electrode current collector. The surface layer may be formed, for example, only on the lattice portion, only on the edge portion, or only on the frame portion of the negative electrode current collector.

[0047] The negative electrode material includes a first organic shrinkage inhibitor and graphite. The negative electrode material includes a negative electrode active material (lead or lead sulfate) that exhibits capacity by an oxidation-reduction reaction. The negative electrode material may include additives other than the first organic shrinkage inhibitor and graphite, as necessary. Examples of additives include a second organic shrinkage inhibitor, a carbonaceous material other than graphite, and barium sulfate. The negative electrode material may include a reinforcing material (such as resin fiber) in addition to these additives. It may include a carbonaceous material other than graphite. In this specification, graphite may be referred to as the first carbonaceous material, and a carbonaceous material other than graphite may be referred to as the second carbonaceous material.

[0048] (First organic shrink-proofing agent) Organic shrink-proofing agents are generally classified into lignin compounds and synthetic organic shrink-proofing agents. Synthetic organic shrink-proofing agents can also be said to be organic shrink-proofing agents other than lignin compounds. The first organic shrink-proofing agent is often a synthetic organic shrink-proofing agent.

[0049] The synthetic organic shrink-proofing agent is an organic compound (e.g., an organic polymer) containing elemental sulfur, and generally contains a plurality of aromatic rings in the molecule and elemental sulfur as a sulfur-containing group. Among the sulfur-containing groups, a sulfonic acid group or a sulfonyl group, which are stable, is preferred. The sulfonic acid group may exist in an acid form or in a salt form such as a Na salt. The first organic shrink-proofing agent preferably contains elemental sulfur in the form of at least a sulfonic acid group or a salt thereof.

[0050] As the first organic shrinkage inhibitor, it is also preferable to use a condensation product containing at least an aromatic compound unit. For example, such a condensation product may be a condensation product of an aromatic compound with an aldehyde compound (at least one selected from the group consisting of aldehydes (e.g., formaldehyde) and condensates thereof). The first organic shrinkage inhibitor may contain one type of aromatic compound unit, or may contain two or more types of aromatic compound units. The aromatic compound unit refers to a unit derived from an aromatic compound incorporated in the condensation product.

[0051] Examples of the aromatic rings that aromatic compounds have include benzene rings and naphthalene rings. When aromatic compounds have multiple aromatic rings, the multiple aromatic rings may be linked by direct bonds or linking groups (e.g., alkylene groups (including alkylidene groups), sulfone groups) and the like. Examples of such structures include bisarene structures (biphenyl, bisphenylalkane, bisphenylsulfone, etc.). Examples of aromatic compounds include compounds having the above aromatic rings and at least one selected from the group consisting of hydroxyl groups and amino groups. The hydroxyl group or amino group may be directly bonded to the aromatic ring, or may be bonded as an alkyl chain having a hydroxyl group or amino group. The hydroxyl group also includes salts of the hydroxyl group (-OMe). The amino group also includes salts of the amino group (specifically, salts with anions). Examples of Me include alkali metals (Li, K, Na, etc.) and metals of Group 2 of the periodic table (Ca, Mg, etc.).

[0052] As the aromatic compound, bisarene compounds [bisphenol compounds, hydroxybiphenyl compounds, bisarene compounds having an amino group (bisarylalkane compounds having an amino group, bisarylsulfone compounds having an amino group, biphenyl compounds having an amino group, etc.), hydroxyarene compounds (hydroxynaphthalene compounds, phenol compounds, etc.), aminoarene compounds (aminonaphthalene compounds, aniline compounds (aminobenzenesulfonic acid, alkylaminobenzenesulfonic acid, etc.)), etc.] are preferred. The aromatic compound may further have a substituent. The first organic shrinkage inhibitor may contain one or more of the residues of these compounds. As the bisphenol compound, bisphenol A, bisphenol S, bisphenol F, etc. are preferred.

[0053] The first organic shrinkage inhibitor may include a condensate containing at least the aromatic compound unit having the above-mentioned sulfur-containing group. The condensate may include at least a bisphenol compound unit as the aromatic compound unit. The sulfur-containing group may be directly bonded to the aromatic ring contained in the compound, or may be bonded to the aromatic ring as an alkyl chain having a sulfur-containing group, for example.

[0054] Also, as the first organic shrinkage inhibitor, for example, at least one condensate containing at least one selected from the group consisting of the above-mentioned bisarene compound units and monocyclic aromatic compound units (hydroxyarene compounds and / or aminoarene compounds, etc.) may be used. The first organic shrinkage inhibitor may at least contain a condensate containing a bisarene compound unit and a monocyclic aromatic compound unit (especially a hydroxyarene compound). Such a condensate may be a condensate of a bisarene compound and a monocyclic aromatic compound with an aldehyde compound. As the hydroxyarene compound, a phenolsulfonic acid compound (such as phenolsulfonic acid or a substituted product thereof) is preferable. As the aminoarene compound, aminobenzenesulfonic acid, alkylaminobenzenesulfonic acid, etc. are preferable. As the monocyclic aromatic compound, a hydroxyarene compound is preferable.

[0055] The negative electrode material may contain one type of first organic shrink-preventing agent or a combination of two or more types.

[0056] The sulfur element content of the first organic shrinkage inhibitor is 2000 μmol / g or more, may be 2500 μmol / g or more, or may be 3000 μmol / g or more. The upper limit of the sulfur element content of the first organic shrinkage inhibitor is not particularly limited, and from the viewpoint of further suppressing the liquid loss, may be 9000 μmol / g or less, 8000 μmol / g or less, or 7000 μmol / g or less.

[0057] The sulfur element content of the first organic shrinkage inhibitor may be 2000 μmol / g or more (or 2500 μmol / g or more) and 9000 μmol / g or less, 2000 μmol / g or more (or 2500 μmol / g or more) and 8000 μmol / g or less, 2000 μmol / g or more (or 2500 μmol / g or more) and 7000 μmol / g or less, 3000 μmol / g or more and 9000 μmol / g or less (or 8000 μmol / g or less), or 3000 μmol / g or more and 7000 μmol / g or less.

[0058] The weight average molecular weight (Mw) of the first organic shrink-proofing agent may be equal to or greater than 7000. The Mw of the first organic shrink-proofing agent may be, for example, equal to or less than 100,000, or equal to or less than 20,000. In this specification, the Mw of the organic shrink-proofing agent is a value measured using sodium polystyrene sulfonate as a standard substance. The Mw of the organic shrink-proofing agent is measured by gel permeation chromatography (GPC).

[0059] The mass ratio of the first organic shrink-proofing agent to the total of the first organic shrink-proofing agent and the second organic shrink-proofing agent is, for example, 50 mass% or more, may be 75 mass% or more, or may be 85 mass% or more. The mass ratio of the first organic shrink-proofing agent is 100 mass% or less.

[0060] (Second organic shrink-proofing agent) The sulfur element content in the second organic shrinkage inhibitor is less than 2000 μmol / g, and may be 1000 μmol / g or less, or 800 μmol / g or less. The lower limit of the sulfur element content in the second organic shrinkage inhibitor is not particularly limited, and is, for example, 400 μmol / g or more.

[0061] Examples of the second organic shrink-proofing agent include a lignin compound and a synthetic organic shrink-proofing agent. Examples of the synthetic organic shrink-proofing agent include the synthetic organic shrink-proofing agents exemplified as the first organic shrink-proofing agent. However, the sulfur element content of the synthetic organic shrink-proofing agent is less than 2000 μmol / g. A lignin compound may be used as the second organic shrink-proofing agent. The negative electrode material may contain one type of the second organic shrink-proofing agent, or two or more types of the second organic shrink-proofing agent.

[0062] Examples of the lignin compound include lignin and lignin derivatives. Examples of the lignin derivative include lignin sulfonic acid or a salt thereof. Examples of the salt of lignin sulfonic acid include an alkali metal salt (such as a sodium salt).

[0063] The Mw of the second organic shrink-proofing agent is, for example, less than 7000. The Mw of the second organic shrink-proofing agent is, for example, 3000 or more.

[0064] The content of the organic shrink-preventing agent in the negative electrode material (the total content of the first organic shrink-preventing agent and the second organic shrink-preventing agent) is, for example, 0.01% by mass or more. The content of the organic shrink-preventing agent is, for example, 1% by mass or less, and may be 0.5% by mass or less. The content of the first organic shrink-preventing agent in the negative electrode material may be in such a range.

[0065] (graphite) The negative electrode material includes graphite (first carbonaceous material). Graphite is a carbonaceous material that includes a graphite-type crystal structure. The graphite may be either artificial graphite or natural graphite. The negative electrode material may include one type of graphite or a combination of two or more types of graphite.

[0066] Graphite often contains Fe element. When graphite containing Fe element is used as a negative electrode material, the negative electrode plate easily reaches the hydrogen generation potential, and the amount of hydrogen gas generated increases. From the viewpoint of easily balancing hydrogen and oxygen and efficiently proceeding with the gas absorption reaction to further reduce the amount of liquid loss, it is preferable to use graphite with a low content of Fe element (including graphite without Fe element). The content of Fe element in graphite may be 200 ppm or less, 190 ppm or less, 110 ppm or less, 70 ppm or less, 50 ppm or less, or 40 ppm or less, based on mass. It is also preferable to use graphite without Fe element. When graphite does not contain Fe element, it also includes the case where the Fe element in graphite is below the detection limit. The effect of suppressing liquid loss obtained by using such graphite with a low content of Fe element is particularly remarkable when the difference (st) is small.

[0067] The graphite content in the negative electrode material is 0.5% by mass or more. The graphite content in the negative electrode material is 2.0% by mass or less, may be 1.2% by mass or less, or may be 1.0% by mass or less. When the graphite content is in this range and the difference (st) is less than 0.10 mm, the amount of solution loss can be reduced when the negative electrode material contains a first organic shrinkage inhibitor.

[0068] In the negative electrode material, the mass ratio of graphite to the total of the graphite and the second carbonaceous material may be 50 mass% or more, 75 mass% or more, or 85 mass% or more. The mass ratio of graphite is 100 mass% or less.

[0069] (Second carbonaceous material) The negative electrode material may contain a second carbonaceous material. Examples of the second carbonaceous material include carbon black, hard carbon, and soft carbon. Examples of carbon black include acetylene black, furnace black, and lamp black. Furnace black also includes Ketjen Black (trade name). The negative electrode material may contain one type of the second carbonaceous material, or may contain two or more types.

[0070] (Barium Sulfate) The negative electrode material may further include barium sulfate. The content of barium sulfate in the negative electrode material may be 0.05% by mass or more, or 0.1% by mass or more. The content of barium sulfate in the negative electrode material may be 3% by mass or less.

[0071] (others) The unformed negative plate is prepared, for example, by applying or filling a negative electrode paste onto a negative electrode current collector, and then aging and drying. The negative electrode active material in a charged state is sponge-like lead, but the unformed negative plate is usually prepared using lead powder. More specifically, the negative electrode paste used to prepare the unformed negative plate is prepared, for example, by adding water and sulfuric acid (or an aqueous sulfuric acid solution) to lead powder, a first organic shrinkage inhibitor, graphite, and other additives (such as a second organic shrinkage inhibitor, a second carbonaceous material, barium sulfate, etc.) as necessary, and kneading them. When aging, it is preferable to age the unformed negative plate at a temperature higher than room temperature and at a high humidity. The negative plate is prepared, for example, by chemically forming the unformed negative plate.

[0072] The formation may be carried out, for example, by placing a plate group including unformed negative plates and an electrolyte containing sulfuric acid in a lead-acid battery container, and charging the plate group in a state in which the electrolyte is saturated with the plate group. However, the formation may also be carried out before assembling the lead-acid battery or the plate group. The formation produces spongy lead.

[0073] (Analysis or measurement of negative electrode material) The analysis or measurement of the negative electrode material is carried out on a negative plate taken from a fully charged lead-acid battery.

[0074] Prior to the analysis or measurement, the negative electrode material is extracted from the negative plate by the following procedure.

[0075] First, a fully charged lead-acid battery is disassembled to obtain a negative plate to be analyzed. The obtained negative plate is washed with water to remove sulfuric acid from the negative plate. The washing is performed by pressing a pH test paper against the washed surface of the negative plate until it is confirmed that the color of the test paper does not change. However, the washing time is within 2 hours. The washed negative plate is dried at 60°C ± 5°C for about 6 hours in a reduced pressure environment. If the negative plate contains an adhesive material after drying, the adhesive material is removed by peeling. The mass of the dried material (negative plate) is measured. Next, the negative electrode material is scraped off from the negative electrode collector and separated to obtain a sample (hereinafter referred to as sample B). Sample B is crushed as necessary and used for analysis of the components of the negative electrode material.

[0076] (Analysis of components in negative electrode materials) (a) Qualitative analysis of organic shrinkage inhibitors in negative electrode materials A predetermined amount of the crushed sample B is collected, weighed, and immersed in 1 mol / L NaOH aqueous solution to extract the organic shrink-preventing agent. Next, the first organic shrink-preventing agent and the second organic shrink-preventing agent are separated from the extract. For each of the separated products containing the organic shrink-preventing agents, insoluble components are removed by filtration, and the resulting solution (hereinafter also referred to as solution C) is desalted, concentrated, and dried. Desalting is performed using a desalting column, or by passing solution C through an ion exchange membrane, or by placing solution C in a dialysis tube and immersing it in distilled water. This is dried to obtain a powder of the organic shrink-preventing agent (hereinafter also referred to as sample D).

[0077] The organic shrinkage inhibitor is identified by combining information obtained from the infrared spectrum of sample D, the ultraviolet-visible absorption spectrum of a solution obtained by dissolving sample D in distilled water or the like, the Nuclear Magnetic Resonance (NMR) spectrum of a solution obtained by dissolving sample D in a solvent such as heavy water, or gas chromatography mass spectrometry (GC-MS) which can obtain information on the individual compounds that make up the substance.

[0078] The first and second organic shrink-preventing agents are separated from the extract as follows. First, the extract is measured by infrared spectroscopy, NMR, and / or GC-MS to determine whether it contains multiple organic shrink-preventing agents. Next, the molecular weight distribution of the extract is measured by GPC. If the multiple organic shrink-preventing agents can be separated by molecular weight, the organic shrink-preventing agents are separated by column chromatography based on the difference in molecular weight. If separation based on the difference in molecular weight is difficult, one of the organic shrink-preventing agents is separated by precipitation separation using the difference in solubility that differs depending on the type and / or amount of functional groups that the organic shrink-preventing agents have. Specifically, the extract is dissolved in an aqueous NaOH solution, and an aqueous sulfuric acid solution is dropped into the mixture to adjust the pH of the mixture, thereby flocculating and separating one of the organic shrink-preventing agents. The separated material is dissolved again in an aqueous NaOH solution, and insoluble components are removed by filtration as described above. The remaining solution after separating one of the organic shrink-preventing agents is concentrated. The resulting concentrate contains the other organic shrinkage inhibitor, and the insoluble components are removed from the concentrate by filtration as described above.

[0079] (b) Quantitative determination of the content of organic shrinkage inhibitor in the negative electrode material As in (a) above, for each of the separated products containing the organic shrinkage inhibitor, insoluble components are removed by filtration to obtain solution C. For each of the obtained solutions C, the ultraviolet-visible absorption spectrum is measured. The content of each organic shrinkage inhibitor in the negative electrode material is determined using the intensity of the peak characteristic of each organic shrinkage inhibitor and a calibration curve prepared in advance.

[0080] In addition, when a lead-acid battery with an unknown content of organic shrink-proofing agent is obtained and the content of the organic shrink-proofing agent is measured, the structural formula of the organic shrink-proofing agent cannot be precisely specified, so that the same organic shrink-proofing agent cannot be used for the calibration curve. In this case, the content of the organic shrink-proofing agent is measured using the ultraviolet-visible absorption spectrum by creating a calibration curve using the organic shrink-proofing agent extracted from the negative electrode of the battery and a separately available organic compound that shows similar shapes in the ultraviolet-visible absorption spectrum, infrared spectroscopy spectrum, and NMR spectrum.

[0081] (c) Sulfur content in organic shrinkage inhibitor As in (a) above, a powder sample D of the organic shrink-proofing agent is obtained, and then the sulfur element in 0.1 g of the organic shrink-proofing agent is converted to sulfuric acid by the oxygen combustion flask method. At this time, the powder sample is burned in a flask containing an adsorption solution to obtain an eluate in which sulfate ions are dissolved in the adsorption solution. Next, the sulfur element content (C1) in 0.1 g of the organic shrink-proofing agent is determined by titrating the eluate with barium perchlorate using thorin as an indicator. Next, C1 is multiplied by 10 to calculate the sulfur element content (μmol / g) in the organic shrink-proofing agent per 1 g.

[0082] (d) Quantitative determination of carbonaceous materials A predetermined amount of the crushed sample B is taken and the mass is measured. 30 mL of nitric acid solution with a concentration of 60% by mass per 5 g of sample B is added to this sample B and heated at 70°C ± 5°C. 10 g of disodium ethylenediaminetetraacetate, 30 mL of ammonia water with a concentration of 28% by mass, and 100 mL of water are added to the resulting mixture with respect to 5 g of sample B, and heating is continued to dissolve the soluble matter. In this way, sample B is pretreated. The dispersion obtained by the pretreatment is filtered using a membrane filter (0.1 μm mesh) to recover the solid matter. The recovered sample is sieved through a 500 μm mesh to remove large-sized components (such as reinforcing materials), and the components that passed through the sieve are recovered as carbonaceous material. The mass of the recovered carbonaceous material is measured.

[0083] When the recovered carbonaceous material is wet sieved using a sieve with 32 μm mesh, the material that does not pass through the sieve and remains on the sieve is called the first carbonaceous material, and the material that passes through the sieve is called the second carbonaceous material. In other words, the particle size of each carbonaceous material is based on the size of the sieve mesh. For information on wet sieving, see JIS Z8815:1994.

[0084] Specifically, the carbonaceous material is placed on a sieve with 32 μm mesh, and sieved by gently shaking the sieve for 5 minutes while spraying ion-exchanged water. The first carbonaceous material remaining on the sieve is collected from the sieve by pouring ion-exchanged water over it, and separated from the ion-exchanged water by filtration. The second carbonaceous material that passed through the sieve is collected by filtration using a nitrocellulose membrane filter (0.1 μm mesh). The collected first and second carbonaceous materials are each dried at a temperature of 100°C ± 5°C for 2 hours. As the sieve with 32 μm mesh, one having a sieve mesh with a nominal mesh size of 32 μm as specified in JIS Z 8801-1:2006 is used.

[0085] The mass of the recovered first carbonaceous material is measured. The ratio (mass%) of this mass to the measured mass of sample B is calculated as the content (mass%) of the first carbonaceous material (graphite) in the negative electrode material. The proportion of the first carbonaceous material in the total of the first carbonaceous material and the second carbonaceous material is calculated by calculating the ratio (mass%) of the measured mass of the first carbonaceous material to the mass of the carbonaceous materials recovered above.

[0086] (e)Fe content The Fe content in the graphite is measured by ICP emission spectrometry of the first carbonaceous material (graphite) separated from the negative electrode material. Specifically, a predetermined amount (about 1 g) of the first carbonaceous material separated in (d) above is collected and its mass is measured. The entire amount of the collected sample is heated in perchloric acid together with periodic acid by wet oxidation decomposition until white smoke is generated, and completely dissolved. The obtained solution is cooled to 25°C, and hydrogen peroxide solution is dropped to precipitate iodine, and the iodine is removed by heating. The liquid components including perchloric acid are evaporated and removed from the remaining solution, and the solution is dried. Distilled water is added to the obtained residue to prepare an aqueous solution, and the emission intensity of Fe in the aqueous solution is measured using an ICP emission spectrometer. The mass of Fe contained in the solution is then calculated using a calibration curve prepared in advance. The ratio (percentage) of the obtained Fe mass to the mass of the first carbonaceous material subjected to analysis is calculated as the Fe content of the graphite (ppm based on mass). The ICP emission spectrometer used is ICPS-8000 manufactured by Shimadzu Corporation.

[0087] (f) Determination of barium sulfate 50 ml of 20% by mass nitric acid is added to 10 g of the crushed sample B, and the mixture is heated for about 20 minutes to dissolve the lead components as lead nitrate. Next, the solution containing lead nitrate is filtered to separate the solids such as carbonaceous materials and barium sulfate.

[0088] The obtained solid content is dispersed in water to obtain a dispersion, and then a sieve is used to remove components other than the carbonaceous material and barium sulfate (e.g., reinforcing material) from the dispersion. Next, the dispersion is subjected to suction filtration using a membrane filter whose mass has been measured in advance, and the membrane filter together with the filtered sample is dried in a dryer at 110°C ± 5°C. The obtained sample is a mixed sample of the carbonaceous material and barium sulfate (hereinafter referred to as sample E). The mass of sample E is measured by subtracting the mass of the membrane filter from the total mass of sample E and the membrane filter after drying. Then, sample E after drying is placed in a crucible together with the membrane filter and incinerated at 1300°C or higher. The remaining residue is barium oxide. The mass of barium oxide is converted to the mass of barium sulfate to determine the mass of barium sulfate.

[0089] (Separator) A separator may be disposed between the negative electrode plate and the positive electrode plate, and may be made of at least one material selected from a nonwoven fabric and a microporous membrane.

[0090] A nonwoven fabric is a mat in which fibers are intertwined without being woven, and is mainly composed of fibers. For example, 60% or more by mass of the nonwoven fabric is made of fibers. As the fibers, glass fibers, polymer fibers (polyolefin fibers, acrylic fibers, polyester fibers (polyethylene terephthalate fibers, etc.), pulp fibers, etc. can be used. Among them, glass fibers are preferable. The nonwoven fabric may contain components other than fibers (for example, acid-resistant inorganic powder, polymers as binders), etc.

[0091] The microporous membrane is a porous sheet mainly composed of components other than fiber components, and can be obtained, for example, by extruding a composition containing a pore-forming agent into a sheet, and then removing the pore-forming agent to form pores. The microporous membrane is preferably made of an acid-resistant material, and is preferably a microporous membrane mainly composed of a polymer component. The polymer component is preferably polyolefin (polyethylene, polypropylene, etc.). The pore-forming agent can be at least one selected from the group consisting of polymer powder and oil.

[0092] The separator may be, for example, composed of only a nonwoven fabric or only a microporous membrane. Furthermore, the separator may be, as necessary, a laminate of a nonwoven fabric and a microporous membrane, a laminate of different or the same materials, or a laminate of different or the same materials with recesses and projections interlocked.

[0093] The separator may be in a sheet shape or may be formed in a bag shape. A sheet-shaped separator may be sandwiched between the positive electrode plate and the negative electrode plate. Also, the electrode plate may be sandwiched between a folded sheet-shaped separator. In this case, the positive electrode plate sandwiched between the folded sheet-shaped separator and the negative electrode plate sandwiched between the folded sheet-shaped separator may be stacked, or one of the positive electrode plate and the negative electrode plate may be sandwiched between the folded sheet-shaped separator and stacked with the other electrode plate. Also, the sheet-shaped separator may be folded into a bellows shape, and the positive electrode plate and the negative electrode plate may be sandwiched between the bellows-shaped separator so that the separator is interposed between them. When a separator folded like an accordion is used, the separator may be arranged so that the folded portion is along the horizontal direction of the lead-acid battery (for example, so that the folded portion is parallel to the horizontal direction) or along the vertical direction (for example, so that the folded portion is parallel to the vertical direction). In a separator folded like an accordion, recesses are formed alternately on both main surfaces of the separator. Since the upper portions of the positive and negative plates usually have lugs, when the separator is arranged so that the folded portion is along the horizontal direction of the lead-acid battery, the positive and negative plates are arranged only in the recesses on one main surface side of the separator (that is, a double separator is interposed between the adjacent positive and negative plates). When the separator is arranged so that the folded portion is aligned with the vertical direction of the lead-acid battery, the positive electrode plate can be accommodated in the recess on one main surface side, and the negative electrode plate can be accommodated in the recess on the other main surface side (that is, a single layer of separator can be interposed between adjacent positive and negative electrode plates.) When a pouch-shaped separator is used, the pouch-shaped separator may accommodate either the positive or negative electrode plate.

[0094] The separator may have at least a first rib protruding toward the positive electrode plate. More specifically, the separator may have a base portion and a first rib protruding from one surface of the base portion toward the positive electrode plate. The presence of the first rib makes it easier for the gas absorption reaction to occur, and can further suppress the loss of liquid. The separator may further have a second rib protruding from the other surface of the base portion toward the negative electrode plate. Each of the first rib and the second rib is formed in a portion facing the electrode material.

[0095] The average height of the first rib may be 0.3 mm or more. From the viewpoint of ensuring a high capacity, the average height of the first rib may be 1.0 mm or less, or may be 0.7 mm or less.

[0096] The separator may have a plurality of first ribs. The plurality of first ribs may extend, for example, along the longitudinal direction of the separator. In this specification, the longitudinal direction of the separator refers to the direction along the vertical direction of the flooded lead-acid battery housing the separator (in other words, the height direction of the plate). The acute angle between the average direction in which the first ribs extend and the height direction of the plate (or the vertical direction in the flooded lead-acid battery) is, for example, 30° or less, and may be 15° or less. The average direction in which the first ribs extend and the height direction of the plate (or the vertical direction in the lead-acid battery) may be parallel.

[0097] The average spacing between the first ribs may be 1.3 cm or less. From the viewpoint of facilitating the formation of a more closed space between the base portion and the positive electrode plate between adjacent first ribs, the average spacing between the first ribs may be 1.0 cm or less. The average spacing between the first ribs refers to the average spacing between adjacent first ribs. The average spacing between the first ribs may be 4 mm or more.

[0098] The average spacing of the first ribs is measured using a separator sample A for measurement. More specifically, the spacing between adjacent first ribs is measured with a vernier caliper at multiple locations on the separator included in the electrode plate group, and then averaged. If the battery includes multiple electrode plate groups, the average spacing of the first ribs is determined for one of the outermost electrode plate groups and one of the electrode plate groups near the center, and then averaged.

[0099] The average height of the second rib may be 0.10 mm or less. The average height of the second rib may be 0.02 mm or more. From the viewpoint of efficiently carrying out the gas absorption reaction on the negative electrode plate side, it is preferable that the average height of the second rib is low, for example, 0.05 mm or less. The separator may not have the second rib.

[0100] The separator may have a plurality of second ribs. The plurality of second ribs may extend along the longitudinal direction of the separator in the same manner as the first rib. The average spacing between the plurality of second ribs may be selected from the ranges described for the first rib. S

[0101] The separator may have a rib (third rib) other than the first rib on the main surface (first main surface) on which the first rib is formed. The third rib is a rib formed in an area of ​​the first main surface that does not face the positive electrode material. The separator may also have a rib (fourth rib) formed in an area of ​​the main surface (second main surface) opposite to the main surface on which the first rib is formed, that does not face the negative electrode material, as necessary. When the separator has a second rib, the second rib is formed in an area of ​​the second main surface that faces the negative electrode material.

[0102] The average thickness of the base portion may be 0.10 mm or more, or may be 0.15 mm or more. The average thickness of the base portion may be 0.30 mm or less.

[0103] (electrolyte) The electrolyte is an aqueous solution containing sulfuric acid. The electrolyte may contain a polymer that swells in the electrolyte, if necessary. The electrolyte is preferably fluid at the temperature at which it is used, and more preferably liquid at 25°C.

[0104] The electrolytic solution may contain cations (e.g., metal cations) and / or anions (e.g., anions other than sulfate anions (e.g., phosphate ions)) as necessary. Examples of metal cations include at least one selected from the group consisting of Na ions, Li ions, Mg ions, and Al ions.

[0105] From the viewpoint of further suppressing the permeation short circuit, the concentration of the metal cation in the electrolyte may be 0.03 mol / L or more. From the viewpoint of ensuring high charge acceptance in regenerative charging, the concentration of the metal cation in the electrolyte may be 0.5 mol / L or less, 0.3 mol / L or less, or 0.1 mol / L or less.

[0106] The density of the electrolyte in a fully charged lead-acid battery at 20°C is, for example, 1.20 g cm -3 The density of the electrolyte at 20°C is 1.35 g cm -3 Here, the density of the electrolytic solution is the density of the electrolytic solution (more specifically, an aqueous sulfuric acid solution) in a state that does not contain additives such as metal cations that are added to the electrolytic solution.

[0107] (others) A lead-acid battery may include one cell or may include two or more cells. When a lead-acid battery includes multiple cells (in other words, multiple plate groups), the multiple plate groups may be connected in series.

[0108] The ratio Ra (=(S1-Sg) / Sg=Se / Sg) may be 0.30 or less. From the viewpoint of further suppressing the loss of electrolyte, the ratio Ra may be 0.25 or less, or 0.24 or less, or may be 0.20 or less. From the viewpoint of ensuring higher PSOC life performance, the ratio Ra is preferably 0.20 or less. The wall surface (side wall or partition wall) of the cell chamber is close to the periphery of the electrode plate group, and the volume in which the electrolyte can be retained is limited. When the ratio Ra is 0.20 or less, the electrolyte present outside the electrode plate group is relatively small, and the upward convection of the electrolyte between the electrode plate group and the battery case wall that occurs during charging is easily blocked. Therefore, it is considered that stratification is suppressed and deterioration of the electrode plate is suppressed, thereby obtaining high PSOC life performance.

[0109] The ratio Ra is determined at a portion parallel to the bottom of the cell chamber (or battery case) of a fully charged lead-acid battery, and 4.5 cm to 5.5 cm above the bottom of the cell chamber (more specifically, the inner bottom surface). Based on this determination method, in this specification, the cross section parallel to the bottom of the cell chamber where the ratio Ra is determined is treated as the cross section of a flooded lead-acid battery at a position parallel to the bottom of the cell chamber of a fully charged lead-acid battery, and 5 cm above the bottom of the cell chamber (more specifically, the inner bottom surface).

[0110] More specifically, the ratio Ra can be found by the following procedure. First, the cross-sectional area S1 inside the cell chamber (or battery case) is found by the following procedure. After removing the electrode plate group and electrolyte from the battery case, the battery case is washed with water, dried, and then placed on a flat surface. Water is then poured in parallel to the bottom of the battery case up to a height of 4.5 cm from the bottom. Next, water is poured in up to a height of 5.5 cm from the bottom, and the volume of the water poured in (cm 3 ) is calculated by dividing the volume of the added water by the height of 1 cm. 2 If the battery case is divided into multiple cells, the cross-sectional area (cm2) of the inside of all the cells is calculated in the same manner as for the battery case. 2 ) by the number of cell chambers to obtain the cross-sectional area S1 (cm 2In addition, in a lead-acid battery, if there are parts other than the plate group and the electrolyte inside the battery case or cell chamber (for example, other members such as spacers and hollow parts (spaces not filled with electrolyte, etc.)), the cross-sectional area S1 inside the battery case or cell chamber is found using the above procedure with these parts present.

[0111] The plate group taken out of the fully charged lead-acid battery is disassembled into the positive plate, the negative plate, and the separator, and the thickness of the positive plate, the thickness of the negative plate, and the total thickness of the separator are obtained by the above-mentioned procedure. However, at this time, the thickness of each plate is measured with a vernier caliper at a position corresponding to a height of 5 cm from the bottom (more specifically, the inner bottom surface) of the cell chamber (or battery case). The thickness of the positive plate × the number of positive plates, the thickness of the negative plate × the number of negative plates, and the total thickness of the separator × the number between the positive plate and the negative plate (in the case of a bag-shaped separator, the total thickness of the separator × the number of bag-shaped separators × 2) are measured and added together. This determines the thickness (dimension y) of the plate group in the stacking direction (y direction). Next, the width (dimension in the x direction) of the plate at a height of 5 cm from the bottom (more specifically, the inner bottom surface) of the cell chamber (or battery case) is measured with a scale. When the widths of the positive and negative plates are different, the average width is calculated and used as the plate width (dimension in the x direction of the plate group). The cross-sectional area Sg of the plate group is calculated by multiplying this plate width by the thickness (dimension y) of the plate group in the stacking direction. The total thickness of the separator corresponds to the sum of the separator thicknesses t mentioned above.

[0112] From S1 and Sg, Se=S1-Sg is calculated. Then, the ratio Ra is calculated by dividing Se by Sg. In a lead-acid battery containing multiple cells, the ratio Ra is calculated by averaging the ratios Ra calculated for the cells located at the ends and the cells located near the center.

[0113] When calculating the ratio Ra, the following points should be noted: First, even when pressure is applied to the plate assembly in the thickness direction, a gap may exist between the plate assembly and the battery case (or cell chamber). For example, if the outermost member is a separator with ribs on its outer surface, and the ribs face the side wall or partition wall of the battery case, the height of the separator ribs is not included in the y-direction dimension of the plate assembly. On the other hand, if the tip of the rib is in contact with the side wall or partition wall, the height of the rib controls the y-direction dimension of the cross-sectional area Sg of the plate assembly. Since the separator ribs have a certain degree of flexibility, they may be deformed by being pressed by the side wall or partition wall. In that case, the height of the rib after deformation controls the y-direction dimension of the cross-sectional area Sg of the plate assembly.

[0114] Similarly, when determining the dimension in the y direction of the cross-sectional area Sg of the electrode plate pack, if the side wall or partition of the battery case has ribs, the height of the ribs is not included in the dimension in the y direction. If both the side wall or partition and the separator have ribs and the tips of the ribs are in contact with the side wall or partition, the sum of the height of the separator rib (the height of the rib after deformation if it is deformed) and the height of the rib of the side wall or partition determines the dimension in the y direction of the cross-sectional area Sg of the electrode plate pack.

[0115] In a lead-acid battery, the opening of the battery case is usually closed with a lid. The lid includes, for example, a negative electrode terminal and a positive electrode terminal. The lid may have a single structure (single lid) or a double structure including an inner lid and an outer lid (or a top lid). A lid having a double structure may include a reflux structure between the inner lid and the outer lid for returning the electrolyte to the inside of the battery (inside the inner lid) from a reflux port provided in the inner lid.

[0116] The lead-acid battery can be obtained, for example, by a manufacturing method including a step of housing a plate group and an electrolyte in a cell chamber of a battery case. Each cell of the lead-acid battery includes a plate group and an electrolyte housed in each cell chamber. The plate group is assembled, for example, by stacking a positive electrode plate, a negative electrode plate, and a separator such that the separator is interposed between the positive electrode plate and the negative electrode plate prior to housing in the cell chamber. Each of the positive electrode plate, the negative electrode plate, and the separator is usually prepared prior to assembly of the plate group. The electrolyte is prepared prior to housing in the cell chamber. When the lead-acid battery has one plate group, the battery case does not need to be divided into a plurality of cell chambers, and the plate group and the electrolyte may be housed in the battery case.

[0117] The method for producing a lead-acid battery may include, after the step of housing the electrode plate group and the electrolyte in the cell chamber, a step of forming at least one of the positive electrode plate and the negative electrode plate, as necessary.

[0118] An external appearance and an internal structure of an example of a flooded lead-acid battery according to one aspect of the present invention are shown in Fig. 1. However, the lead-acid battery according to one aspect of the present disclosure is not limited to the following embodiment.

[0119] The flooded lead-acid battery 1 includes a battery case 12 that contains a plate group 11 and an electrolyte (not shown). The inside of the battery case 12 is divided into a plurality of cell chambers 14 by partition walls 13. Each cell chamber 14 contains one of the plate groups 11. The opening of the battery case 12 is closed by a lid 15 that includes a positive electrode terminal 16 and a negative electrode terminal 17. The lid 15 is provided with a vent plug 18 for each cell chamber. When refilling with water, the vent plug 18 is removed and refilling liquid is added. The vent plug 18 may have a function of discharging gas generated in the cell chamber 14 to the outside of the battery.

[0120] The electrode plate group 11 is formed by alternately stacking a plurality of negative electrode plates 3 and positive electrode plates 2 with separators 4 interposed therebetween. Here, the separator 4 is bag-shaped and packs the positive electrode plates 2 one by one. However, the form of the separator is not particularly limited. In the cell chamber 14 located at one end of the battery case 12, the positive electrode shelf 6 that connects the ears 2a of the plurality of positive electrode plates 2 in parallel is connected to the through connector 8, and the negative electrode shelf 5 that connects the ears 3a of the plurality of negative electrode plates 3 in parallel is connected to the negative electrode column 7. The negative electrode column 7 is connected to a negative electrode terminal 17 outside the lid 15. In the cell chamber 14 located at the other end of the battery case 12, the positive electrode column 9 is connected to the positive electrode shelf 6, and the through connector 8 is connected to the negative electrode shelf 5. The positive electrode column 9 is connected to a positive electrode terminal 16 outside the lid 15. Each of the through-connectors 8 passes through a through hole provided in the partition wall 13 and connects the electrode plate groups 11 of adjacent cell chambers 14 in series.

[0121] The positive electrode shelf 6 is formed by welding, for example, by a cast-on-strap method or a burning method, the ears 2a provided on the upper part of each positive electrode plate 2. The negative electrode shelf 5 is also formed by welding, in the same manner as the positive electrode shelf 6, the ears 3a provided on the upper part of each negative electrode plate 3.

[0122] Although the lid 15 of the lead-acid battery has a single structure (single lid), this is not limited to the illustrated example. For example, the lid 15 may have a double structure as described above. The lid having a double structure may have a reflux structure.

[0123] [Example] The present invention will be specifically described below based on examples and comparative examples, but the present invention is not limited to the following examples.

[0124] Flooded lead-acid batteries E1 to E51 and C1 to C76 (1) Preparation of lead-acid batteries (a) Preparation of the negative electrode plate Lead powder, water, dilute sulfuric acid, an organic shrinkage inhibitor (first organic shrinkage inhibitor or second organic shrinkage inhibitor) having a sulfur element content shown in the table, barium sulfate, carbon black, and graphite are mixed to obtain a negative electrode paste. At this time, the amounts of each component are adjusted so that the contents of the organic shrinkage inhibitor, barium sulfate, and carbon black in the negative electrode material obtained by the above-mentioned procedure are 0.2 mass%, 0.6 mass%, and 0.3 mass%, respectively, and the graphite content is the value shown in the table. The negative electrode paste is filled into the mesh part of an expanded lattice made of a Pb-Ca-Sn alloy and aged and dried. In this way, an unformed negative electrode plate is obtained. The Fe content in the graphite obtained by the above-mentioned procedure is 190 ppm by mass in Tables 1 and 2, and the value shown in each table in Tables 3 and 4.

[0125] (b) Preparation of the positive electrode plate Lead powder, water, and dilute sulfuric acid are mixed to obtain a positive electrode paste. The positive electrode paste is filled into the mesh of an expanded grid made of Pb-Ca-Sn alloy as a positive electrode current collector, and then aged and dried. In this way, an unformed positive electrode plate is obtained.

[0126] (c) Fabrication of flooded lead-acid battery The battery has a nominal voltage of 12 V (6 cells) and a rated 20-hour rate capacity of 60 Ah. The battery plate group is composed of seven positive plates and eight negative plates. First, the unformed positive plates are placed in a pouch-shaped separator and stacked alternately with the negative plates. The resulting plate group composed of unformed plates is placed in a battery container together with an electrolyte (aqueous sulfuric acid solution) and formed in the container to produce a liquid-type lead-acid battery. In Tables 1 to 3, the specific Ra is adjusted using a spacer so that it is 0.24 as determined by the procedure described above, and in Table 4, the specific Ra is adjusted to the value shown in Table 4. The density of the electrolyte in a fully charged lead-acid battery at 20°C is 1.285 g cm without additives such as metal cations. -3 The above chemical conversion brings the lead-acid battery into a fully charged state.

[0127] (2) Evaluation The following evaluations are performed using batteries with a nominal voltage of 12 V (6 cells) produced in the Examples or Comparative Examples. When the following evaluations are performed using other batteries, the evaluations are performed at a voltage that matches the number of cells in the battery.

[0128] (a) Amount of liquid reduction Measure the mass of the battery (M0). Place the battery in a water bath at 60°C ± 2°C and charge it at a constant voltage of 14.4 V with a maximum current of 50 A for 42 days. When the liquid level reaches the minimum liquid level line during charging, add water up to the maximum liquid level line and record the amount of water added. After charging, remove the battery from the water bath and leave it to reach room temperature (20-35°C), then measure the mass of the battery (M1). Subtract M1 from M0 to obtain the total amount of water added (M a ) to calculate the amount of battery loss. In Tables 1 and 4, the amount of battery C16 is set to 100, and in Table 3, the amount of battery C14 is set to 100, and the amount of battery loss is evaluated as a relative value. The smaller this relative value, the more suppressed the loss of battery life is.

[0129] (b) High temperature resistance For each battery whose mass M1 was measured in (a) above, test it at a temperature of -18°C ± 2°C for 100×I 20 Discharge (high rate discharge) at a constant current of (A) and measure the time (discharge duration) until the battery terminal voltage reaches 6V. The longer the discharge duration, the better the high temperature resistance. The high temperature resistance of each battery is evaluated as a relative value when the discharge duration of battery C16 is set as 100.

[0130] (c) PSOC life performance The PSOC life performance of flooded lead-acid batteries is evaluated by the following procedure. All steps are carried out in a water bath at 25°C ± 1°C. Steps 1 to 7 are repeated. The charge in step 2 and the discharge in step 3 are counted as one cycle, and the number of cycles when the end-of-discharge voltage in step 3 falls below 10 V is determined. The PSOC life performance of each battery is evaluated as a relative value when the number of cycles of battery E19 is set to 100. A larger value indicates a more excellent PSOC life performance. Step 1 (conditioning discharge): Discharge for 2.5 hours at a current of 4 x I20A. Step 2 (charging): Set the upper limit current to 7 x I20A and charge at a constant voltage of 14.4V for 40 minutes. Step 3 (discharge): Discharge at a current of 7 x I20A for 30 minutes. Step 4: Repeat steps 2 and 3 for 85 cycles. Step 5 (charging): Set the upper limit current to 2 x I20A and charge at a constant voltage of 16.0V for 18 hours. Step 6 (Discharge): Discharge at a current of I20A until the voltage reaches 10.5V. Step 7 (charging): Set the upper limit current to 5 x I20A and charge at a constant voltage of 16.0V for 24 hours.

[0131] The evaluation results are shown in Tables 1 to 4. In these tables, E1 to E51 are examples, and C1 to C76 are comparative examples.

[0132] [Table 1]

[0133] As shown in Table 1, when (st) ≧ 0.10 mm, the tendency of liquid loss does not change even if the graphite content changes. When (st) < 0.10 mm, if a first organic shrink-proofing agent is used, the tendency of liquid loss at a graphite content of 0 mass% is almost the same as when (st) ≧ 0.10 mm. However, when (st) < 0.10 mm, if a first organic shrink-proofing agent is used and the graphite content is 0.5 mass% or more and 2.0 mass% or less, liquid loss can be significantly suppressed. [Table 2]

[0134] As shown in Table 2, when the first organic shrink-preventing agent is used, higher high temperature resistance is obtained than when the second organic shrink-preventing agent is used.

[0135] [Table 3]

[0136] As shown in Table 3, the lower the Fe content in the graphite, the smaller the amount of liquid loss. Also, when (st) ≧ 0.10 mm, the amount of liquid loss is greater when the first organic shrink-proofing agent is used than when the second organic shrink-proofing agent is used. On the other hand, when (st) < 0.10 mm, the amount of liquid loss is less when the first organic shrink-proofing agent is used than when the second organic shrink-proofing agent is used. When the Fe content is low, the amount of liquid loss is particularly small.

[0137] [Table 4]

[0138] As shown in Table 4, when Ra≦0.20, the amount of liquid loss is further reduced compared to when Ra>0.20. Also, when Ra≦0.20, the PSOC life performance is significantly improved compared to when Ra>0.20. [Industrial Applicability]

[0139] The flooded lead-acid battery according to one aspect of the present invention is suitable for use as an IS lead-acid battery in a vehicle equipped with an idle reduction system. The lead-acid battery can also be suitably used as a starting power source for a vehicle (such as an automobile or motorcycle) or an industrial power storage device (such as a power source for an electric vehicle (such as a forklift)). Note that these are merely examples, and the uses of the flooded lead-acid battery are not limited to these. [Explanation of symbols]

[0140] 1: Liquid lead acid battery 2: Positive electrode plate 2a: Positive electrode plate lug 3: Negative plate 3a: Negative electrode plate lug 4: Separator 5: Negative electrode shelf 6: Positive electrode shelf 7: Negative pole 8: Through connector 9: Positive pole 11: Plate group 12:Battery container 13: Bulkhead 14: Cell Room 15: Lid 16: Positive terminal 17: Negative terminal 18: Liquid outlet plug

Claims

1. A flooded lead-acid battery, The flooded lead-acid battery includes a plate group, an electrolyte, and a cell chamber that accommodates the plate group and the electrolyte, the electrode plate group includes a positive electrode plate, a negative electrode plate, and a separator interposed between the positive electrode plate and the negative electrode plate, The difference between the total distance s between the positive electrode plate and the negative electrode plate facing each other in the electrode plate group and the total thickness t of the separator: (s−t) is less than 0.10 mm; The negative electrode plate includes a negative electrode material, The negative electrode material includes an organic shrinkage preventer having a sulfur element content of 2000 μmol / g or more and graphite, The content of the graphite in the negative electrode material is 0.5 mass % or more and 2.0 mass % or less.

2. 2. The flooded lead-acid battery of claim 1, wherein the difference (s−t) is 0.07 mm or less.

3. 3. The flooded lead-acid battery according to claim 1, wherein in a cross section of the flooded lead-acid battery parallel to a bottom of the cell chamber, a ratio Ra (=Se / Sg) of an area Se (=S1-Sg) obtained by subtracting a cross-sectional area Sg of the plate pack from a cross-sectional area S1 inside the cell chamber to the cross-sectional area Sg of the plate pack is 0.20 or less.

4. 3. The flooded lead-acid battery according to claim 1, wherein the separator has a rib that protrudes toward at least the positive electrode plate.

5. 5. The flooded lead-acid battery of claim 4, wherein the average spacing between the ribs is 1.0 cm or less.

6. 3. The flooded lead-acid battery according to claim 1, wherein the graphite does not contain elemental Fe, or the content of elemental Fe in the graphite is 110 ppm or less by mass.

Citation Information

Patent Citations

  • Lead storage battery

    WO2011142072A1

  • Lead acid storage battery, vehicle with start-stop system, and micro-hybrid vehicle

    WO2019077657A1

  • Lead acid storage battery

    WO2019188056A1

  • Lead-acid battery

    WO2019225161A1